2020
DOI: 10.33963/kp.15604
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis in high-risk patients with left-sided obstructive prosthetic valve thrombosis

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives 4.0 International License (CC BY-NC-ND 4.0), allowing third parties to download articles and share them with others, provided the original work is properly cited, not changed in any way, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Showkathali et al, [27] reported that the mortality ratio in the event of surgery was as high as, while it was as high as 16% in the case of TT. Because of the scarcity of surgical products and the high rates, most patients are hesitant to have the procedure redone.…”
Section: Resultsmentioning
confidence: 99%
“…Showkathali et al, [27] reported that the mortality ratio in the event of surgery was as high as, while it was as high as 16% in the case of TT. Because of the scarcity of surgical products and the high rates, most patients are hesitant to have the procedure redone.…”
Section: Resultsmentioning
confidence: 99%